Dialogical Communication in the Qur’an: A Thematic-Hermeneutic Study of Hiwār Verses in Tafsir al-Mishbah - Ahdaa, Muhammad Fauzal; Ibrahim, Muhammad Syahrial Razali; Zaki Faddad Syarif Zain (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study aims to examine the concept of hiwār (dialogue) in the Qur’an through the perspective of Tafsir al-Mishbah by M. Quraish Shihab. The main issue addressed is the decline of communication ethics in the modern era and how the principles of Qur’anic dialogue can serve as a reference for building harmonious communication. Using a thematic-hermeneutic approach, this study seeks to describe the forms, principles, and functions of hiwār based on verses containing dialogue, such as those in QS. al-Kahfi, al-Mujadalah, Ali Imran, Ghafir, al-Hajj, and al-Syura. The method employed is a descriptive-analytical qualitative approach through direct analysis of Tafsir al-Mishbah and other supporting references. The results of the study indicate that dialogue in the Qur’an is rational, ethical, and solution-oriented; it emphasizes the importance of knowledge, humility, and the prohibition of baseless debate. Furthermore, the concept of ushul marji’iyah—adherence to the Qur’an and Sunnah—emerges as a fundamental principle in resolving differences. These findings affirm that the dialogue method from the perspective of Tafsir al-Mishbah is relevant for application in contemporary social and digital communication to prevent conflict and strengthen the value of brotherhood. This study contributes to the formulation of an applicable framework for Qur’anic communication ethics, emphasizing that hiwār is not merely theological in nature but also possesses a social dimension relevant to addressing the communication crisis in the modern era, particularly within the digital space, which is prone to conflict and disinformation. This makes this study relevant not only for academic research but also for the development of more inclusive and harmonious communication practices.